THE EFFECTIVENESS OF IMPLEMENTING ISLAMIC LEADERSHIP IN BMT CIVIL SOCIETY OF NORTH SUMATRA - Basyar, Hibban; Mella, Sinta Misda; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine the effectiveness of the application of Islamic leadership in the Civil Society BMT of North Sumatra. This research was carried out using qualitative research consisting of interviews, observation and documentation. The results of this research show that the Islamic leadership of North Sumatra Civil Society BMT (MASDA SUMUT) is one of the sharia financial services cooperatives that plays a role in increasing community economic empowerment. Islamic leadership BMT Civil Society of North Sumatra (MASDA SUMUT) uses a type or model of leadership in which this leadership provides freedom in completing tasks or work, provides confidence in the work of its employees, provides freedom of opinion, provides opportunities to provide suggestions for a decision. Leadership in Islam does not only explain that a leader must carry out his leadership with the rules that a leader must have. Islam means that leaders who carry out their leadership must also be accompanied by love in guiding and controlling the people. It can be concluded that the application of Islamic leadership has provided positive results in several aspects such as Economic Empowerment, Transparency and Accountability, and improving the quality of human resources.